Composite powder, positive electrode composite material, and alkali metal ion battery

By using a composite powder containing carbon materials, alkaline metal ionic electrical materials and monocular sulfur in the alkaline metal ion battery, solve the problem of small discharge capacity of batteries at high current density, realize better multiplied characteristics and lithium ion conductivity sex.

CN119384731APending Publication Date: 2025-01-28IDEMITSU KOSAN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380047143.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing alkali metal ion batteries have small discharge capacity under high current density and poor magnification characteristics, especially the lithium ion conductivity of sulfur-carbon composites.

Method used

Use carbon materials containing fine pores, the first hoting material and the composite powder with the second heat -content material. By heating, it melts and is immersed in the fine pores of carbon material.

Benefits of technology

A significant increase in the discharge capacity and magnification characteristics of the alkaline metal ion battery at high current density, and enhance the conductivity of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384731A_ABST
    Figure CN119384731A_ABST
Patent Text Reader

Abstract

The present invention relates to a composite powder comprising a carbon material having pores, and a first heat-impregnated material and a second heat-impregnated material which are present in the pores, the first heat-impregnated material comprising an alkali metal ion conductive material or a precursor thereof, and the second heat-impregnated material comprising an alkali metal ion conductive material or a precursor thereof. The alkali metal ion conductive material or the precursor thereof contains one or more elements selected from among lithium, boron, oxygen, phosphorus, halogen, and antimony, and the second thermal impregnation material contains elemental sulfur.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite powder, a positive electrode composite material, and an alkali metal ion battery containing the composite powder. Background Art

[0002] In alkali metal ion batteries such as lithium ion batteries and sodium ion batteries, it is desired that the battery capacity is excellent at a high current density. Regarding battery capacity, a method of using sulfur for a positive electrode due to its large theoretical capacity has been studied (for example, refer to Non-Patent Document 1). However, since sulfur has low electronic conductivity, when sulfur is used for a positive electrode, it is necessary to ensure electronic conductivity by some method.

[0003] In order to solve the above-mentioned technical problems, a composite of sulfur and a carbon material having pores has been studied (for example, refer to Patent Document 1 and Non-Patent Document 2).

[0004] On the other hand, since the diffusion of alkali metal ions in sulfur is slow, there is a technical problem that the sulfur-carbon composite has a small discharge capacity (low rate characteristic) at a high current density.

[0005] It is disclosed that when a sulfur-carbon complex is used for the positive electrode of an all-solid lithium battery, a composite of a carbon material, sulfur and a solid electrolyte is prepared by mechanically mixing a solid electrolyte having high lithium ion conductivity with the sulfur-carbon complex or by using a solution obtained by dissolving the solid electrolyte (for example, see Patent Documents 2-4). However, the lithium ion conductivity in the pores is still low, and the discharge capacity (rate characteristics) at a high current density cannot be said to be sufficient.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 5856979

[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-68663

[0010] Patent Document 3: Japanese Patent Application Publication No. 2015-79622

[0011] Patent Document 4: Japanese Patent Application Publication No. 2020-161288

[0012] Non-patent literature

[0013] Non-patent document 1: An All-solid-state Sodium-Sulfur Battery Operating at Room Temperature Using a High-sulfur-content Positive Composite Electrode, Chem. Lett., 2014, 43, 1333-1334.

[0014] Non-patent document 2: A highly ordered nanostructured carbon-sulphur cathode for lithium-sulphur batteries, Nature Materials, 2009, 8, 500-506. Summary of the invention

[0015] An object of the present invention is to provide a composite powder capable of improving the discharge capacity (rate characteristics) of an alkali metal ion battery at a high current density.

[0016] According to the present invention, the following composite powder and the like are provided.

[0017] 1. A composite powder comprising a carbon material having pores, and a first hot impregnation material and a second hot impregnation material present in the pores,

[0018] The first heat impregnation material includes an alkali metal ion conductive material or a precursor thereof, wherein the alkali metal ion conductive material or the precursor thereof includes one or more elements selected from lithium, boron, oxygen, phosphorus, halogen, and antimony.

[0019] The second heat impregnation material includes elemental sulfur.

[0020] 2. The composite powder according to item 1, wherein the melting point of the first thermal impregnation material is 130 to 950°C.

[0021] 3. The composite powder according to 1 or 2, wherein the first thermal impregnation material and the second thermal impregnation material are melted and impregnated into the pores.

[0022] 4. The composite powder as described in any one of 1 to 3, wherein the first thermal impregnation material is selected from phosphorus pentasulfide, red phosphorus, boron sulfide, lithium sulfide, lithium polysulfide (Li2S n, n satisfies 1<n≤8), one or more compounds selected from the group consisting of lithium halide, lithium borohydride, lithium oxide, phosphorus pentoxide, boron oxide, trilithium phosphate and antimony sulfide.

[0023] 5. The composite powder according to any one of 1 to 4, wherein the BET specific surface area of ​​the carbon material is 50 m 2 / g above 6000m 2 / g or less.

[0024] 6. The composite powder according to any one of 1 to 5, wherein the pore volume of the carbon material is 0.5 cm 3 / g above 6cm 3 / g or less.

[0025] 7. A positive electrode composite material comprising the composite powder as described in any one of 1 to 6 and a solid electrolyte.

[0026] 8. An alkali metal ion battery comprising the composite powder as described in any one of 1 to 6.

[0027] 9. A method for producing a composite powder, comprising carrying out the following steps (1) and (2) simultaneously or separately,

[0028] Step (1): a step of heating the carbon material having pores and the alkali metal ion conductive material containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony or a precursor thereof at a temperature not lower than the melting point;

[0029] Step (2): a step of heating the carbon material and elemental sulfur at a temperature not lower than the melting point of elemental sulfur.

[0030] 10. The production method according to 9, wherein the melting point of the alkali metal ion conductive material or its precursor is 130 to 950°C.

[0031] 11. The production method according to 9 or 10, wherein the step (2) is performed after the step (1).

[0032] According to the present invention, it is possible to provide a composite powder capable of improving the discharge capacity (rate characteristics) of an alkali metal ion battery at a high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 These are the SEM image and EDX mapping of the cross section of the composite powder A (carbon element (C), phosphorus element (P), and sulfur element (S)).

[0034] Figure 2A The second cycle (discharge current density: 0.187 mA cm-2 , Charging: 0.187mAcm -2 )’s charge and discharge curve.

[0035] Figure 2B The eighth cycle (discharge current density: 7.46 mA cm -2 , Charging: 0.373mAcm -2 )’s charge and discharge curve.

[0036] Figure 3 This is a graph showing the rate characteristics of the batteries produced in Example 1 and Comparative Examples 1 and 2.

[0037] Figure 4 It is a graph showing the cycle characteristics of the batteries prepared in Example 1 and Comparative Examples 1 and 2.

[0038] Figure 5A The second cycle of the battery prepared in Examples 2 to 4 (discharge current density: 0.187 mA cm -2 , Charging: 0.187mAcm -2 )’s charge and discharge curve.

[0039] Figure 5B The eighth cycle (discharge current density: 7.46 mA cm -2 , Charging: 0.373mAcm -2 )’s charge and discharge curve.

[0040] Figure 6 This is a graph showing the rate characteristics of the batteries produced in Examples 2 to 4.

[0041] Figure 7 This is a graph showing the cycle characteristics of the batteries produced in Examples 2 to 4.

[0042] Figure 8 These are the SEM image and EDX mapping (carbon element (C) and iodine element (I)) of the cross section of the composite powder G.

[0043] Fig. 9 These are the SEM image and EDX mapping (carbon element (C) and antimony element (Sb)) of the cross section of the composite powder I.

[0044] Fig. 10A The second cycle of the battery prepared in Example 5 (discharge current density: 0.187 mA cm -2 , Charging: 0.187mAcm -2 )’s charge and discharge curve.

[0045] Fig. 10BThe 8th cycle of the battery prepared in Example 5 (discharge current density: 7.46 mA cm -2 , Charging: 0.373mAcm -2 )’s charge and discharge curve.

[0046] Fig.11 This is a graph showing the rate characteristics of the battery produced in Example 5.

[0047] Fig.12 This is a graph showing the cycle characteristics of the battery produced in Example 5.

[0048] Fig.13 These are the SEM image and EDX mapping (carbon element (C) and bromine element (Br)) of the cross section of the composite powder K.

[0049] Fig.14 These are the SEM image and EDX mapping (carbon element (C) and phosphorus element (P)) of the cross section of the composite powder M. DETAILED DESCRIPTION

[0050] A composite powder according to one embodiment of the present invention comprises a carbon material having pores, and a first hot impregnation material and a second hot impregnation material present in the pores, wherein the first hot impregnation material comprises an alkali metal ion conductive material or a precursor thereof, wherein the alkali metal ion conductive material or a precursor thereof comprises one or more elements selected from lithium, boron, oxygen, phosphorus, halogens and antimony, and the second hot impregnation material comprises elemental sulfur.

[0051] In this embodiment, the first hot impregnation material and the second hot impregnation material, which are heated to become melts, are infiltrated into the pores of the carbon material to fill the pores. That is, the hot impregnation material is melted and impregnated into the pores without using a solvent or diluting the hot impregnation material. As a result, the first hot impregnation material and the second hot impregnation material can be fully enclosed in the pores, and the rate characteristics are improved.

[0052] On the other hand, an impregnation method has been disclosed so far, in which an alkali metal ion conductive material such as a solid electrolyte is dissolved in a solvent to form a solution, and the solution is filled into the pores of a carbon material, and then the alkali metal ion conductive material is precipitated (for example, see Patent Document 4). In this impregnation method, since a solvent is used, it is believed that since the impregnation material is diluted, a sufficient amount of the alkali metal ion conductive material cannot be impregnated into the pores, and thus the rate characteristics cannot be greatly improved.

[0053] In addition, in the method of mechanically mixing the solid electrolyte into the sulfur-carbon composite, since the solid electrolyte does not enter the pores of the carbon material impregnated with sulfur, a conductive path for the alkali metal ions cannot be formed, and the alkali metal ion conductivity in the pores is only brought about by the diffusion of the alkali metal ions in the sulfur. As a result, it is believed that the rate characteristics cannot be improved.

[0054] In the present embodiment, the first heat impregnation material includes a material having alkali metal ion conductivity or a precursor thereof, and the material having alkali metal ion conductivity or a precursor thereof includes one or more elements selected from lithium, boron, oxygen, phosphorus, halogens, and antimony.

[0055] In this specification, "alkali metal ion conductive material containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony" refers to a material that remains solid at 25°C under a nitrogen atmosphere and has ion conductivity caused by alkali metal ions. In addition, "precursor of alkali metal ion conductive material containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony" refers to a substance that reacts with an alkali metal or an alkali metal ion to form a compound containing an alkali metal when used as an active material of an alkali metal ion battery, thereby becoming the above-mentioned alkali metal ion conductive material.

[0056] In this specification, the above-mentioned “alkali metal ion conductive material” and “precursor of alkali metal ion conductive material” may be collectively referred to as “alkali metal ion conductive material or its precursor”.

[0057] In the present specification, examples of "halogen" include elements such as fluorine, chlorine, bromine and iodine.

[0058] From the point of view of being made into a melt by heating, the melting point of the first heat impregnation material is preferably 130 to 950° C., and more preferably 220 to 950° C. In addition, the melting point of the first heat impregnation material is preferably a lower temperature such as 850° C. or less, 750° C. or less, 650° C. or less, 600° C. or less, or 550° C. or less. By lowering the temperature in the process, the energy during the manufacturing process can be reduced, thereby achieving cost reduction.

[0059] As the alkali metal ion conductive material, when the alkali metal is lithium, lithium sulfide, lithium polysulfide (Li2S n , n satisfies 1<n≤8), lithium halide (LiCl, LiBr, LiI, etc.), lithium borohydride, lithium oxide, trilithium phosphate, lithium sulfate, lithium carbonate, LiBF4, lithium tetraborate, organic lithium salt, lithium hydroxide, etc. In addition, as precursors of lithium ion conductive materials, phosphorus pentasulfide, red phosphorus, boron sulfide, phosphorus pentoxide, boron oxide, antimony sulfide, antimony, tin sulfide, tin, germanium sulfide, bismuth sulfide, etc. can be cited. These compounds can be used alone, and two or more can also be used in combination.

[0060] When the alkali metal is sodium, sodium polysulfide, sodium halide (NaCl, NaBr, NaI, etc.), sodium borohydride, sodium sulfate, sodium carbonate, NaBF4, sodium tetraborate, organic sodium salt, sodium hydroxide, etc. can be cited. In addition, as the precursor of the sodium ion conductive material, the same substances as the precursor of the above-mentioned lithium ion conductive material can be cited. These compounds can be used alone, and two or more can also be used in combination.

[0061] As the organic lithium salt, there may be mentioned bis(perfluoroalkylsulfonyl)imide lithium salts such as lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl-trifluoromethanesulfonylimide, lithium bis(pentafluoroethanesulfonyl)imide, and lithium bis(nonafluorobutanesulfonyl)imide; lithium salts of perfluoroalkylsulfonyl imides such as lithium 4,4,5,5-tetrafluoro-1,3,2-dithiazolidine-1,1,3,3-tetraoxide; lithium salts of fluorosulfonyl imides; lithium salts of carboxylates such as trifluoromethanesulfonic acid, lithium acetate, lithium propionate, and lithium butyrate; organic sulfonic acid lithium salts such as lithium dodecylbenzenesulfonate and lithium p-styrenesulfonate; organic lithium phosphates, and the like.

[0062] These organic lithium salts are preferably used together with an ion conductive polymer or an ionic liquid, and can be expected to impart higher lithium conductivity.

[0063] The organic sodium salt may be one obtained by replacing lithium ions of the above-mentioned organic lithium salts with sodium ions.

[0064] The first hot impregnation material is preferably selected from phosphorus pentasulfide, red phosphorus, boron sulfide, lithium sulfide, lithium polysulfide (Li2S n , n satisfies 1<n≤8), one or more compounds selected from the group consisting of lithium halide, lithium borohydride, lithium oxide, phosphorus pentoxide, boron oxide, trilithium phosphate and antimony sulfide.

[0065] Particularly preferred are phosphorus pentasulfide or boron sulfide, which are expected to react with lithium to form a sulfide solid electrolyte showing high ion conductivity; or lithium halide, which is reported to form a solid solution with lithium sulfide, which is a discharge product of sulfur, thereby improving the lithium ion conductivity of lithium sulfide.

[0066] In this embodiment, examples of the carbon material having pores include carbon black such as Ketjen black, acetylene black, superconductive acetylene black (Denka Black), thermal black, channel black, CNovel (registered trademark), graphite, activated carbon, etc. These may be used alone or in combination of two or more.

[0067] In one embodiment, the BET specific surface area of ​​the carbon material is 50 m 2 / g above 6000m 2This can form a wide contact interface between the carbon material and elemental sulfur, and can improve the utilization rate of sulfur.

[0068] The BET specific surface area is preferably 70 m 2 / g or more, more preferably 100m 2 / g or more, 1000m 2 / g or more, 1500m 2 / g or more. In addition, preferably 5500m 2 / g or less, more preferably 5000m 2 / g or less.

[0069] In addition, the pore volume of the carbon material is 0.5 cm 3 / g above 6cm 3 This allows a large amount of elemental sulfur to be impregnated into the pores of the carbon material together with the ion conductive material or its precursor, and the capacity of the battery can be further increased.

[0070] The pore volume is preferably 0.7 cm 3 / g or more, more preferably 1.0 cm 3 / g or more. In addition, it is preferably 5.5cm 3 / g or less, more preferably 5.0cm 3 / g or less.

[0071] In the present invention, the BET specific surface area and the pore volume can be obtained by using a nitrogen adsorption isotherm obtained by adsorbing nitrogen gas on a carbon material at a liquid nitrogen temperature. Specifically, the BET specific surface area can be calculated by the Brenauer-Emmet-Telle (BET) multi-point method using a nitrogen adsorption isotherm. In addition, the pore volume can be obtained by using a Barret-Joyner-Halenda (BJH) method using a nitrogen adsorption isotherm.

[0072] As a measuring device, for example, a specific surface area and pore size distribution measuring device (Autosorb-3) manufactured by Quantachrome Technologies Inc. can be used for measurement.

[0073] The composite powder of the present embodiment can be produced by heating a carbon material having pores, a first hot impregnation material, and a second hot impregnation material (hereinafter, the first hot impregnation material and the second hot impregnation material are sometimes collectively referred to as hot impregnation materials) at a temperature above the melting point of each hot impregnation material.

[0074] Specifically, the carbon material, the first heat impregnation material, and the second heat impregnation material are mixed, and the mixture is heated to melt the first heat impregnation material and the second heat impregnation material, thereby impregnating the first heat impregnation material and the second heat impregnation material into the pores of the carbon material. In this embodiment, the first heat impregnation material and the second heat impregnation material can be impregnated into the carbon material at the same time. In addition, in one embodiment, the first heat impregnation material and the second heat impregnation material can also be impregnated into the carbon material separately. For example, after the first heat impregnation material is impregnated into the carbon material, the second heat impregnation material can be impregnated.

[0075] The mixing ratio of the carbon material and the heat impregnation material can be appropriately adjusted according to the material used. Usually, the mixing ratio of the carbon material [carbon material / (carbon material+first heat impregnation material+second heat impregnation material): mass ratio] is 0.073 to 0.990. If it is within this range, the heat impregnation material is fully filled into the pores of the carbon material. Preferably, it is 0.077 to 0.950, and more preferably, it is 0.081 to 0.905.

[0076] The mixture of the carbon material and the hot impregnation material is heated at a temperature above the melting point of the hot impregnation material. The heating temperature is adjusted according to the hot impregnation material used. For a material that has sublimation properties under normal pressure, it can be pressurized and hot impregnated. The heating time is preferably 10 minutes to 24 hours.

[0077] Composite powder can be obtained by heating and then cooling. If necessary, a pulverization step may be performed after cooling.

[0078] In this embodiment, it is preferred that the following steps (1) and (2) are performed simultaneously or separately.

[0079] Step (1): a step of heating the carbon material having pores and the alkali metal ion conductive material containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony or a precursor thereof at a temperature not lower than the melting point;

[0080] Step (2): a step of heating the carbon material and elemental sulfur at a temperature not lower than the melting point of elemental sulfur.

[0081] In one embodiment, in step (1), it is preferred that the alkali metal ion conductive material or its precursor having a melting point of 130 to 950° C. is heated to a temperature equal to or higher than the melting point.

[0082] In one embodiment, step (2) is performed after step (1). This allows sufficient alkali metal ion conductive material or a precursor thereof to be impregnated into the pores of the carbon material without being affected by the melt of elemental sulfur.

[0083] In step (2), the mixing ratio of the carbon material [carbon material / (carbon material+elemental sulfur): mass ratio] is preferably 0.075 to 0.990, more preferably 0.078 to 0.951, and even more preferably 0.082 to 0.906.

[0084] When an alkali metal ion conductive material or a precursor thereof containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony and elemental sulfur are simultaneously impregnated into a carbon material, the mixing ratio of the carbon material [carbon material / (carbon material + alkali metal ion conductive material or a precursor thereof containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony + elemental sulfur): mass ratio] is 0.073 to 0.990.

[0085] The heating temperature in step (2) is not less than the melting point of elemental sulfur (about 115°C), preferably not less than 130°C, and more preferably not less than 150°C.

[0086] The heating in step (2) may be carried out in two or more stages. For example, the heating temperature in the first stage may be set to be above the melting point of elemental sulfur and below the melting point of the alkali metal ion conductive material or its precursor, and the heating temperature in the second stage may be set to be above the melting point of the alkali metal ion conductive material or its precursor. This makes it easy to impregnate sufficient elemental sulfur and the alkali metal ion conductive material or its precursor into the pores of the carbon material.

[0087] The composite powder of the present invention can be used as a constituent material of an alkali metal ion battery. The type of alkali metal ion battery is not particularly limited, and for example, a positive electrode composed of a positive electrode composite material including a solid electrolyte and the composite powder can be used.

[0088] An alkali metal ion battery according to one embodiment of the present invention comprises the composite powder of the present invention. For example, a fully solid alkali metal ion battery can be manufactured by using a solid electrolyte instead of a liquid electrolyte. By using the composite powder of the present invention, a fully solid alkali metal ion battery with good rate characteristics can be manufactured. Hereinafter, as an example of a fully solid alkali metal ion battery, a fully solid lithium ion battery is described.

[0089] The all-solid lithium ion battery is mainly composed of a positive electrode layer, a negative electrode layer and an electrolyte layer, and the composite powder of the present invention is preferably used as a constituent material of the positive electrode layer. The negative electrode layer and the electrolyte layer can be manufactured by a known method. In addition, in addition to the positive electrode layer, the negative electrode layer and the electrolyte layer, a current collector is preferably used, and a known current collector can be used.

[0090] The solid electrolyte is not particularly limited, and for example, a sulfide solid electrolyte may be mentioned.

[0091] The sulfide solid electrolyte is a solid electrolyte that contains at least sulfur atoms and exhibits ionic conductivity caused by the metal ions contained therein. In addition to sulfur atoms, it preferably also contains lithium atoms and phosphorus atoms, and more preferably also contains lithium atoms, phosphorus atoms and halogen atoms, and is a solid electrolyte with ionic conductivity caused by lithium atoms.

[0092] The sulfide solid electrolyte may be an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte.

[0093] (Amorphous sulfide solid electrolyte)

[0094] As an amorphous sulfide solid electrolyte, any amorphous sulfide solid electrolyte can be used without particular limitation as long as it contains at least sulfur atoms and exhibits ionic conductivity caused by the metal ions contained therein. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes such as Li2S-P2S5 composed of lithium sulfide and phosphorus sulfide, containing sulfur atoms, lithium atoms and phosphorus atoms; solid electrolytes such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr composed of lithium sulfide, phosphorus sulfide and lithium halide; and solid electrolytes such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc., which also contain other elements such as oxygen and silicon. From the viewpoint of obtaining higher ion conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr, are preferred.

[0095] The types of elements constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0096] When the amorphous sulfide solid electrolyte has at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 65-85:15-35, more preferably 70-80:20-30, and further preferably 72-78:22-28 from the viewpoint of high chemical stability and higher ion conductivity.

[0097] For example, when the amorphous sulfide solid electrolyte is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0098] In the amorphous sulfide solid electrolyte, when lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms are contained, the blending ratio (molar ratio) of these atoms is preferably 1.0 to 1.8: 1.0 to 2.0: 0.1 to 0.8: 0.01 to 0.6, more preferably 1.1 to 1.7: 1.2 to 1.8: 0.2 to 0.6: 0.05 to 0.5, and further preferably 1.2 to 1.6: 1.3 to 1.7: 0.25 to 0.5: 0.08 to 0.4.

[0099] In addition, when bromine and iodine are used in combination as halogen atoms, the blending ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine atoms and iodine atoms is preferably 1.0-1.8: 1.0-2.0: 0.1-0.8: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 1.2-1.8: 0.2-0.6: 0.02-0.25: 0.02-0.25, more preferably 1.2-1.6: 1.3-1.7: 0.25-0.5: 0.03-0.2: 0.03-0.2, and further preferably 1.35-1.45: 1.4-1.7: 0.3-0.45: 0.04-0.18: 0.04-0.18. By setting the mixing ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, a solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure described later and having higher ion conductivity can be easily obtained.

[0100] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) For example, the range of 0.01 μm to 500 μm and 0.1 to 200 μm can be exemplified.

[0101] In this specification, the average particle size (D 50 ) is the particle size when the cumulative particle size distribution curve is drawn, starting from the smallest particle and accumulating to reach 50% of the total. The volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device.

[0102] (Crystalline sulfide solid electrolyte)

[0103] As the crystalline sulfide solid electrolyte, for example, so-called glass ceramics obtained by heating the above-mentioned amorphous sulfide solid electrolyte to a crystallization temperature or higher may be used. A sulfide solid electrolyte having the following crystal structure can be used.

[0104] Examples of the crystal structure that a crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, and phosphorus atoms may have include Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0105] In addition, examples of the crystal structure that the crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms may have include Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). Here, "thio-LISICON Region II type crystal structure" means Li 4- x Ge 1-x P x S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4- x Ge 1-x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.

[0106] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0107] In addition, as the crystal structure of the crystalline sulfide solid electrolyte, the argyrodite type crystal structure can also be cited. As the argyrodite type crystal structure, for example, the Li7PS6 crystal structure can be cited; the Li7PS6 structure skeleton having the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y The crystal structure represented by S6 (x is -0.6 to 0.6, y is 0.1 to 0.6); 7-x-2y PS 6-x-y Cl x The crystal structure represented by (0.8≤x≤1.7, 0<y≤-0.25x+0.5); 7-x PS 6-x Ha x (Ha is Cl or Br, and x is preferably 0.2 to 1.8)

[0108] Among the above-mentioned crystal structures, the crystal structure possessed by the crystalline sulfide solid electrolyte is preferably a Li3PS4 crystal structure, a sulfide crystalline lithium superion conductor region type II crystal structure, or an argyrodite-type crystal structure.

[0109] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape. The average particle size (D 50 ) and the average particle size (D 50 ) Similarly, for example, it can be exemplified within the range of 0.01 μm to 500 μm and 0.1 to 200 μm.

[0110] Example

[0111] Hereinafter, the present invention will be described in detail based on examples, but the present invention is not limited to the examples.

[0112] Example 1

[0113] [Production of composite powder]

[0114] (1) Preparation of composite powder A

[0115] Activated carbon (MSC-30, manufactured by Kansai Thermochemical Co., Ltd.) and phosphorus pentasulfide (manufactured by Italmatch Chemicals Co., Ltd., melting point 286-290°C) were placed in a carbon particle heating tube with an inner diameter of 12 mm at a mass ratio of 68:32, and then sealed in a SUS tube container. The temperature was raised from room temperature to 350°C in an electric furnace for 1 hour, and then maintained at 350°C for 6 hours to obtain composite powder A.

[0116] The average particle size of the activated carbon (MSC-30) used is D 50 50 to 150 μm (product catalog value), pore volume is 1.58 cm 3 / g, BET specific surface area is 2840m 2 The above-mentioned pore volume and BET specific surface area are values ​​of pores having a pore diameter of 100 nm or less in the porous carbon.

[0117] The pore volume and BET specific surface area were measured using a specific surface area and pore distribution measuring device (Autosorb-3) manufactured by Quantachrome.

[0118] The composite powder A was subjected to argon ion milling to expose the particle cross section, and then SEM-EDX analysis was performed to confirm the impregnation state of phosphorus pentasulfide into the activated carbon.

[0119] Figure 1The following are the SEM images and EDX mapping (carbon (C), phosphorus (P) and sulfur (S)) of the cross section of composite powder A. Figure 1 It was confirmed that phosphorus pentasulfide was impregnated into the pores of the activated carbon due to the presence of the P element and the S element on the cross section of the activated carbon confirmed as the C element.

[0120] (2) Preparation of composite powder B

[0121] The composite powder A and elemental sulfur (melting point 115°C) were placed in a carbon particle heating tube with an inner diameter of 12 mm at a mass ratio of 39:61, and then sealed in a SUS tube container. The composite powder A and sulfur composite powder B were obtained by heating at 150°C for 6 hours in an electric furnace and then at 300°C for 2.75 hours.

[0122] [Production of positive electrode composite material]

[0123] (1) Preparation of solid electrolyte

[0124] 0.4127g of lithium sulfide, 0.6655g of phosphorus pentasulfide, 0.2137g of lithium iodide, 0.2080g of lithium bromide, and 10 zirconia balls with a diameter of 10mm were put into a 45mL zirconia can and sealed. A planetary ball mill (manufactured by FRITSCH, model P-7) was used to mix (mechanically grind) at a speed of 370rpm for 40 hours to obtain a powder. The obtained powder was heated at 195°C for 3 hours to obtain a solid electrolyte.

[0125] (2) Preparation of positive electrode composite materials

[0126] 0.51 g of composite powder B and 0.45 g of solid electrolyte were put into a 45 mL zirconia can with 10 zirconia balls with a diameter of 10 mm, and sealed. A planetary ball mill (FRITSCH, model P-7) was used to mix the mixture at 370 rpm for 20 hours at room temperature to obtain a positive electrode composite material powder.

[0127] [Manufacturing of lithium-ion batteries (all-solid-state batteries)]

[0128] 60 mg of the above-made solid electrolyte was put into a cylinder made of MACOR (glass ceramic) with a diameter of 10 mm and pressurized. 5.4 mg of the above-made positive electrode composite material powder was put into the pressurized surface and pressurized again. An all-solid-state battery was made by putting indium foil and lithium foil into the pressurized surface opposite to the positive electrode composite material and pressurizing.

[0129] Comparative Example 1

[0130] (1) Preparation of composite powder

[0131] Activated carbon (MSC-30) and elemental sulfur were placed in a glass tube at a mass ratio of 30:70, and then sealed in a SUS tube container, and heated at 150° C. for 6 hours and then at 300° C. for 2.75 hours in an electric furnace to obtain a composite powder.

[0132] (2) Fabrication of positive electrode composite materials and lithium-ion batteries

[0133] Using 0.45 g of the composite powder of (1), 0.064 g of phosphorus pentasulfide, and 0.45 g of the solid electrolyte prepared in Example 1 as raw material powders, a positive electrode composite material was prepared under the same preparation conditions as in Example 1. In addition, an all-solid-state battery was prepared under the same conditions as in Example 1.

[0134] Comparative Example 2

[0135] Using 0.32 g of elemental sulfur, 0.14 g of activated carbon (MSC-30), 0.064 g of phosphorus pentasulfide, and 0.45 g of the solid electrolyte prepared in Example 1 as raw material powders, a positive electrode composite material was prepared under the same production conditions as in Example 1. In addition, an all-solid-state battery was prepared under the same production conditions as in Example 1.

[0136] [Evaluation of battery characteristics]

[0137] A constant current charge and discharge test was performed on the all-solid batteries prepared in Example 1 and Comparative Examples 1 and 2. The voltage range of the charge and discharge test was set to 0.8-2.2 V vs. Li-In, and the current density was set to the conditions shown in Table 1.

[0138] [Table 1]

[0139]

[0140] Figure 2A The second cycle of Example 1, Comparative Examples 1 and 2 (current density during discharge: 0.187 mA cm -2 )’s charge and discharge curve, Figure 2B The 8th cycle (current density during discharge: 7.46 mA cm) of Example 1, Comparative Examples 1 and 2 -2 )’s charge and discharge curve.

[0141] Figure 3 is a graph showing the discharge capacity (rate characteristics) at high current density, Figure 4 It is a graph showing cycle characteristics.

[0142] 2 to 4 , when comparing the battery characteristics of the example and the comparative example, it can be confirmed that the battery of the example shows a large discharge capacity at a high current density (excellent rate characteristics) and also has good cycle characteristics.

[0143] Example 2

[0144] (1) Preparation of composite powder C

[0145] Composite powder C was obtained under the same conditions as those for preparing composite powder A in Example 1, except that the mass ratio of activated carbon (MSC-30) to phosphorus pentasulfide was changed to 81:19.

[0146] (2) Preparation of composite powder D

[0147] Composite powder D was obtained under the same conditions as those for preparing composite powder B in Example 1 except that the mass ratio of composite powder C to elemental sulfur was changed to 35:65.

[0148] (3) Fabrication of positive electrode composite materials and lithium-ion batteries

[0149] A positive electrode composite material was prepared using 0.48 g of composite powder D and 0.45 g of the solid electrolyte prepared in Example 1 as raw material powders under the same preparation conditions as in Example 1. A solid-state battery was prepared under the same conditions as in Example 1 except that 5.2 mg of the solid-state battery powder was used.

[0150] Example 3

[0151] (1) Preparation of composite powder E

[0152] Composite powder E was obtained under the same conditions as those for preparing composite powder A in Example 1 except that the mass ratio of activated carbon (MSC-30) to phosphorus pentasulfide was changed to 51:49.

[0153] (2) Preparation of composite powder F

[0154] Composite powder F was obtained under the same conditions as those for preparing composite powder B in Example 1, except that the mass ratio of composite powder E to elemental sulfur was changed to 45:55.

[0155] (3) Fabrication of positive electrode composite materials and lithium-ion batteries

[0156] A positive electrode composite material was prepared using 0.58 g of composite powder F and 0.45 g of the solid electrolyte prepared in Example 1 as raw material powders under the same preparation conditions as Example 1. A solid-state battery was prepared under the same conditions as Example 1 except that 5.7 mg of the positive electrode composite material powder was used.

[0157] Example 4

[0158] (1) Preparation of composite powder G

[0159] Activated carbon (MSC-30) and lithium iodide (melting point 459°C) were placed in a carbon particle heating tube with an inner diameter of 12 mm at a mass ratio of 56:44, and then sealed in a SUS tube container. The temperature was raised from room temperature to 520°C in an electric furnace in 1 hour, and then maintained at 520°C for 6 hours to obtain composite powder G.

[0160] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder G to confirm the impregnation status of the activated carbon with lithium iodide.

[0161] Figure 8 The SEM image and EDX mapping (carbon element (C) and iodine element (I)) of the cross section of composite powder G. Figure 8 It was confirmed that lithium iodide was impregnated into the pores of the activated carbon due to the presence of the I element on the cross section of the activated carbon confirmed as the C element.

[0162] (2) Preparation of composite powder H

[0163] Composite powder H was obtained under the same conditions as those for preparing composite powder B in Example 1, except that the mass ratio of composite powder G to elemental sulfur was changed to 43:57.

[0164] (3) Fabrication of positive electrode composite materials and lithium-ion batteries

[0165] A positive electrode composite material was prepared using 0.56 g of composite powder H and 0.45 g of the solid electrolyte prepared in Example 1 as raw material powders under the same preparation conditions as in Example 1. A solid-state battery was prepared under the same conditions as in Example 1 except that 5.6 mg of the positive electrode composite material powder was used.

[0166] In the same manner as in Example 1, the all-solid-state batteries produced in Examples 2 to 4 were evaluated.

[0167] Figure 5A The second cycle of Examples 2 to 4 (current density during discharge: 0.187 mA cm -2 )’s charge and discharge curve, Figure 5B The 8th cycle of Examples 2 to 4 (current density during discharge: 7.46 mA cm -2 )’s charge and discharge curve.

[0168] Figure 6 is a graph showing the discharge capacity (rate characteristics) at high current density, Figure 7 It is a graph showing cycle characteristics.

[0169] 5 to 7 , it can be confirmed that a large discharge capacity (excellent rate characteristics) is shown at a high current density, and also good cycle characteristics are exhibited.

[0170] Example 5

[0171] (1) Preparation of composite powder I

[0172] Composite powder I was obtained under the same conditions as the preparation of composite powder A in Example 1, except that phosphorus pentasulfide was changed to antimony sulfide (melting point 550°C), the mass ratio of activated carbon (MSC-30) to antimony sulfide was set to 49:51, and the heating temperature was changed to 580°C.

[0173] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder I to confirm the impregnation status of the activated carbon with antimony sulfide.

[0174] Fig. 9 The SEM image and EDX mapping (carbon element (C) and antimony element (Sb)) of the cross section of composite powder I are shown in FIG. Fig. 9 It was confirmed that antimony sulfide was impregnated into the pores of the activated carbon due to the presence of the Sb element on the cross section of the activated carbon confirmed as the C element.

[0175] (2) Preparation of composite powder J

[0176] Composite powder J was obtained under the same conditions as those for preparing composite powder B in Example 1, except that composite powder I was used and the mass ratio of composite powder I to elemental sulfur was changed to 47:53.

[0177] (3) Fabrication of positive electrode composite materials and lithium-ion batteries

[0178] A positive electrode composite material and an all-solid-state battery were prepared under the same production conditions as in Example 1 except that the composite powder J was used as the raw material powder.

[0179] The all-solid-state battery produced in Example 5 was evaluated in the same manner as in Example 1.

[0180] Fig. 10A The second cycle of Example 5 (current density during discharge: 0.187 mA cm -2 )’s charge and discharge curve, Fig. 10B The 8th cycle of Example 5 (discharge current density: 7.46 mA cm -2 )’s charge and discharge curve.

[0181] Fig.11 is a graph showing the discharge capacity (rate characteristics) at high current density, Fig.12It is a graph showing cycle characteristics.

[0182] 10 to 12 , it can be confirmed that the high discharge capacity (excellent rate characteristics) at a high current density is shown, and that the good cycle characteristics are also exhibited.

[0183] Example 6

[0184] (1) Preparation of composite powder K

[0185] Composite powder K was obtained under the same conditions as the preparation of composite powder A in Example 1, except that phosphorus pentasulfide was replaced by lithium bromide (melting point 547°C), the mass ratio of activated carbon (MSC-30) to lithium bromide was set to 56:44, and the heating temperature was changed to 552°C.

[0186] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder K to confirm the impregnation status of the activated carbon with lithium bromide.

[0187] Fig.13 The SEM image and EDX mapping (carbon (C) and bromine (Br)) of the cross section of the composite powder K are shown in FIG. Fig.13 It was confirmed that lithium bromide was impregnated into the pores of the activated carbon due to the presence of the Br element on the cross section of the activated carbon confirmed as the C element.

[0188] (2) Preparation of composite powder L

[0189] Composite powder L was obtained under the same conditions as those for preparing composite powder B in Example 1, except that composite powder K was used and the mass ratio of composite powder K to elemental sulfur was changed to 43:57.

[0190] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder L, and it was confirmed that the activated carbon was impregnated with lithium bromide.

[0191] Example 7

[0192] (1) Preparation of composite powder M

[0193] Composite powder M was obtained under the same conditions as the preparation of composite powder A in Example 1, except that phosphorus pentasulfide was changed to red phosphorus (melting point 589.5°C, sublimation temperature 416°C), the mass ratio of activated carbon (MSC-30) to red phosphorus was set to 67:33, and the heating temperature was changed to 450°C.

[0194] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder M to confirm the impregnation state of phosphorus into the activated carbon.

[0195] Fig.14The SEM image and EDX mapping (carbon element (C) and phosphorus element (P)) of the cross section of the composite powder M are shown in FIG. Fig.14 It was confirmed that phosphorus was impregnated into the pores of the activated carbon due to the presence of the P element on the cross section of the activated carbon confirmed as the C element.

[0196] (2) Preparation of composite powder N

[0197] Composite powder N was obtained under the same conditions as those for preparing composite powder B in Example 1, except that composite powder M was used and the mass ratio of composite powder M to elemental sulfur was changed to 39:61.

[0198] In the same manner as in Example 1, SEM-EDX analysis was performed on the composite powder N, and it was confirmed that the activated carbon was impregnated with red phosphorus.

[0199] Industrial Applicability

[0200] The composite powder of the present invention is preferably used as a constituent material of an alkali metal ion battery, particularly as a positive electrode composite material. In addition, the alkali metal ion battery of the present invention can be preferably used, for example, in batteries used in information-related equipment such as personal computers, cameras and mobile phones, or communication equipment, and vehicles such as electric cars.

[0201] Several embodiments and / or examples of the present invention have been described in detail above, but it is easy for those skilled in the art to add many changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these many changes are included within the scope of the present invention.

[0202] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are cited.

Claims

1. A composite powder, characterized in that: The invention comprises a carbon material having pores, and a first heat impregnation material and a second heat impregnation material existing in the pores. The first heat impregnation material includes an alkali metal ion conductive material or a precursor thereof, wherein the alkali metal ion conductive material or the precursor thereof includes one or more elements selected from lithium, boron, oxygen, phosphorus, halogen, and antimony. The second heat impregnation material includes elemental sulfur.

2. The composite powder according to claim 1, characterized in that The melting point of the first hot impregnation material is 130-950°C.

3. The composite powder according to claim 1 or 2, characterized in that: The first heat impregnation material and the second heat impregnation material are melted and impregnated into the pores.

4. The composite powder according to any one of claims 1 to 3, characterized in that The first hot impregnation material is one or more compounds selected from the group consisting of phosphorus pentasulfide, red phosphorus, boron sulfide, lithium sulfide, lithium polysulfide, lithium halide, lithium borohydride, lithium oxide, phosphorus pentoxide, boron oxide, trilithium phosphate and antimony sulfide, wherein the lithium polysulfide is Li2S n , n satisfies 1<n≤8.

5. The composite powder according to any one of claims 1 to 4, characterized in that The BET specific surface area of ​​the carbon material is 50 m 2 / g above 6000m 2 / g or less.

6. The composite powder according to any one of claims 1 to 5, characterized in that The pore volume of the carbon material is 0.5 cm 3 / g above 6cm 3 / g or less.

7. A positive electrode composite material, characterized in that: The invention comprises the composite powder according to any one of claims 1 to 6 and a solid electrolyte.

8. An alkali metal ion battery, characterized in that: Comprising the composite powder according to any one of claims 1 to 6.

9. A method for producing a composite powder, characterized in that: The following steps (1) and (2) are performed simultaneously or separately, Step (1): a step of heating the carbon material having pores and the alkali metal ion conductive material containing one or more elements selected from lithium, boron, oxygen, phosphorus, halogen and antimony or a precursor thereof at a temperature not lower than the melting point; Step (2): a step of heating the carbon material and elemental sulfur at a temperature not lower than the melting point of elemental sulfur.

10. The manufacturing method according to claim 9, characterized in that: The melting point of the alkali metal ion conductive material or its precursor is 130 to 950°C.

11. The manufacturing method according to claim 9 or 10, characterized in that: The step (2) is carried out after the step (1).

Citation Information

Patent Citations

  • Cowling structure of motorcycle

    JP1983056979A

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Positive electrode mixture, method for manufacturing the same, and all-solid type lithium sulfur battery

    JP2015079622A

  • Sulfur positive electrode mixture and manufacturing method thereof, sulfur positive electrode, and lithium-sulfur solid-state battery

    JP2020161288A

  • Method for producing positive electrode material

    JP2021068663A